Multi-pathway blood biomarkers to target and monitor multidimensional prevention of cognitive and functional decline (nested in the IN-TeMPO study framed within the world-wide FINGERS network) - Sala, Gessica; Cuffaro, Luca; Pozzi, Federico Emanuele; Andreoni, Simona; Bazzini, Chiara; Conti, Elisa; Zoia, Chiara Paola; Beretta, Simone; Tremolizzo, Lucio; Bellelli, Giuseppe; Okoye, Chukwuma; Ferrara, Maria Cristina; et al. (Frontiers in Aging Neuroscience, 2025)
BackgroundAs the population ages, the identification of preventive strategies able to delay cognitive and functional decline associated with aging represents a major challenge. To date, multidimensional approaches seem to be effective in reducing or delaying the onset of age-related diseases.ObjectivesThe multicentric randomized controlled trial IN-TeMPO (ItaliaN study with Tailored Multidomain interventions to Prevent functional and cognitive decline in community-dwelling Older adults, ClinicalTrials.gov ID NCT06248723), framed within the World-Wide FINGERS network, aims to verify the efficacy of guided multidomain interventions in preventing age-related cognitive and functional decline. Within this study, we will explore a comprehensive array of established and exploratory blood biomarkers of several pathologic age-related processes, including Alzheimer’s disease (AD), neurodegeneration, inflammation, senescence and sarcopenia, to stratify subject risk and assess the effect of multidomain interventions on biomarkers.Design and participantsApoE4 status and plasma p-tau217 (AD), NfL (neurodegeneration), GFAP and IL-6 (inflammation), GDF-15 (senescence/sarcopenia) will be evaluated in all subjects (n = 1,662) both at the baseline and at the end of the study (12 months). Exploratory additional biomarkers will be measured at the same time points in a subgroup of 100 subjects: BDNF, ghrelin, IGF-1, irisin and redox status in plasma as markers of sarcopenia/senescence and oxidative stress, gamma-H2AX in PBMCs as marker of senescence, and amyloid beta aggregates in plasma, urine and erythrocytes as supportive markers of AD. Untargeted metabolomics analysis in plasma and untargeted volatilomics analysis in whole blood and urine will be performed to explore molecular alterations that may be associated with the pathogenesis and progression of age-related diseases in frail older adults with the aim of identifying novel potential biomarkers.ConclusionThe comprehensive clinical use of multiple laboratory biomarkers can contribute both to the early identification of trajectories of cognitive and functional decline in older adults, and to the identification of mechanisms underlying the effect of multidisciplinary interventions on age-related pathological processes.